Gasification of Microalgae Using Supercritical Water and the Potential of Effluent Recycling. Issue 2 (14th January 2016) - Elsayed, Sherif; Boukis, Nikolaos; Patzelt, Dominik; Hindersin, Stefan; Kerner, Martin; Sauer, Jörg
Abstract: The gasification of microalgae in supercritical water was investigated in this work. The product gas contained mainly H2, CO2, CH4, and C2 H6 . Operation at high temperatures and lower biomass concentrations resulted in the highest carbon gasification efficiency and the lowest total organic carbon levels in the residual water. Due to its content of inorganic nutrients, the residual water was applied as cultivation medium for microalgae. However, algal growth in the untreated residual water was inhibited by the existence of potentially toxic substances evolved from gasification. Upon treatment by activated carbon filtration and ultraviolet light degradation, these substances were eliminated and cultivation in the residual water was possible. The major fraction of inorganic residues from gasification was recovered by means of water purging, increasing the potential of nutrient recycling for cultivation. Abstract : Gasification of biomass in supercritical water exemplifies the use of renewable sources such as microalgae for energy production. Algal biomass is gasified without drying, yielding a combustible gas mixture. Integration of the cultivation and gasification processes can be carried out by circulating the by‐products from gasification to apply them in microalgae cultivation for biomass production.